Anti-mumps IgM antibody positive rate with sudden sensorineural hearing loss using second-generation enzyme immunoassay: A retrospective, multi-institutional investigation in Hokkaido, Japan. Issue 5 (October 2018) - Fukuda, Atsushi; Morita, Shinya; Nakamaru, Yuji; Hoshino, Kimiko; Fujiwara, Keishi; Akazawa, Shigeru; Sakashita, Tomohiro; Obara, Nobuyuki; Homma, Akihiro
Abstract: Objective: Although elevated anti-mumps IgM antibody levels were reported in 5.7%–7.2% of Japanese patients with sudden sensorineural hearing loss (SSNHL), there were several reports of false-positive cases, such as the continually IgM positive case and the IgM positive case in normal adults. To improve specificity, the new enzyme immuno assay (EIA) anti-mumps IgM antibody measurement kit was introduced in December 2009. This study re-examined the frequency of anti-mumps IgM antibody test positivity with SSNHL using the new measurement kit and compared the results with those from a previous report that used old kit. Methods: This is a retrospective multi-institutional study involving patients diagnosed with SSNHL who exhibited the anti-mumps IgM antibody. We compared the positive rate of anti-mumps IgM antibody and the annual average number of mumps cases per sentinel in Hokkaido between the patients in the present study and patients previously evaluated. Results: Overall, 100 patients with SSNHL were enrolled. One case (1.0%) was positive for anti-mumps IgM antibody. Of the 69 patients evaluated in the previous study, 5 cases (7.2%) were positive for anti-mumps IgM antibody. The positive rate of the anti-mumps IgM antibody in the present cases was significantly lower than that previously reported ( p  = 0.042). The annual average number of mumps cases per sentinel in Hokkaido of the present and previous surveillance period was 34.47 and 42.77, respectively; no significant difference was seen in these data ( p  = 0.4519). Conclusion: The present study revealed that 1.0% of SSNHL was positive for the anti-mumps IgM antibody using the new EIA-IgM measurement kit. After the introduction of the new EIA-IgM measurement kit, anti-mumps IgM antibody positive rate with SSNHL significantly decreased, indicating that the proportion of asymptomatic mumps among etiology of SSNHL may be lower than those previously reported.